2019
DOI: 10.1016/j.envpol.2019.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of some trace elements in tropical mangrove plants and snails (Can Gio, Vietnam)

Abstract: Mangrove sediments can store high amount of pollutants that can be more or less bioavailable depending on environmental conditions. When in available forms, these elements can be subject to an uptake by mangrove biota, and can thus become a problem for human health. The main objective of this study was to assess the distribution of some trace elements (Fe, Mn, Co, Ni, Cr, As, and Cu) in tissues of different plants and snails in a tropical mangrove (Can Gio mangrove Biosphere Reserve) developing downstream a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 84 publications
0
17
1
Order By: Relevance
“…Most suggest a decrease in photosynthesis, growth, and biomass (Maiti and Chowdhury, 2013). Although field observation reports on the low capacity of mangrove plants to absorb most metals, the same may not be true for mangrove animals (Thành-Nho et al, 2019). Notwithstanding, a key issue regarding metal accumulation and eventual harmful effects on mangrove biota depend on metal abundance and availability (Marchand et al, 2011;Lacerda et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Most suggest a decrease in photosynthesis, growth, and biomass (Maiti and Chowdhury, 2013). Although field observation reports on the low capacity of mangrove plants to absorb most metals, the same may not be true for mangrove animals (Thành-Nho et al, 2019). Notwithstanding, a key issue regarding metal accumulation and eventual harmful effects on mangrove biota depend on metal abundance and availability (Marchand et al, 2011;Lacerda et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The potential of plants to remove toxic metals, particularly mangrove plants, has been demonstrated in several studies worldwide [3,93,94]. The researchers discovered that the production of iron plaques on the roots of mangrove plants plays a critical function in preventing Fe and As transfer to the aerial portions [95]. We expressed interest in this venture since some countries, particularly poor countries such as Bangladesh, cannot change the situation overnight because many people rely on the lines of work that pollute our environment regularly.…”
Section: Phytoremediation and Basic Typesmentioning
confidence: 99%
“…Additionally, higher NH 4 concentrations (Taillardat et al, 2019), pCO 2 and CO 2 emissions (David et al, 2018b;Taillardat et al, 2018;Vinh et al, 2019) were measured during the monsoon due to enhanced microbial activity. The monsoon also increased metal loads in the estuary (Thanh-Nho et al, 2018), and it was demonstrated that their transfer to the biota differed between mangrove stands (Thanh-Nho et al, 2019). Consequently in previous studies concerning Can Gio mangrove, we were able to show: (i) the importance of mangrove-derived organic matter in the functioning of this estuary, (ii) the seasonal variability of OM quality and mineralization, (iii) the influence of OM on trace metals cycling; however up to now, the first step of mangrove leaf litter decomposition was not studied.…”
Section: Introductionmentioning
confidence: 99%